MicroRNA‐760 Inhibits Doxorubicin Resistance in Hepatocellular Carcinoma through Regulating Notch1/Hes1‐PTEN/Akt Signaling Pathway. Issue 8 (3rd July 2018) - Tian, Tao; Fu, Xiao; Lu, Jun; Ruan, Zhiping; Nan, Kejun; Yao, Yu; Yang, Yujuan
Abstract: Accumulating studies have suggested that microRNA‐760 (miR‐760) plays an important role in chemoresistance of various cancer cells. However, whether miR‐760 regulates the chemoresistance of hepatocellular carcinoma (HCC) remains unclear. In this study, we found that miR‐760 was decreased in HCC cell lines, and doxorubicin (Dox) treatment significantly decreased miR‐760 expression in HCC cells. Overexpression of miR‐760 sensitized HCC cells to Dox‐induced cytotoxicity and apoptosis, whereas miR‐760 inhibition showed the opposite effects. Notch1 was predicted as a target gene of miR‐760. miR‐760 negatively regulated Notch1 expression and Notch1/Hes1 signaling. Overexpression of miR‐760 increased PTEN expression and decreased the phosphorylation of Akt. Activation of Notch signaling significantly reversed the inhibitory effect of miR‐760 on Dox‐resistance and abrogated the effect of miR‐760 on the PTEN/Akt signaling pathway in HCC cells. Overall, our results demonstrate that miR‐760 inhibits Dox‐resistance in HCC cells through inhibiting Notch1 and promoting PTEN expression.